Realizacja funkcji zarządu mieniem publicznym w prawie zamówień publicznych - Guziński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
When ordering in the form of a contract for consideration by public entities things, works, services used to perform public tasks, the provisions of the Public Procurement Law introduce a specific procedure regime, bearing in mind the public good (protection of public property). At the same time, these rules concern the assessment and correction of the behavior of entities managing public property. This indicates that the analyzed provisions of the law, which in certain cases are a kind of procedure for spending public funds, serve to perform the function of managing public property.
Keywords: public property; managing public property; public procurement law; awarding entity